Modeling the Corrosion Inhibition of Mild Steel in HCl Medium with the Inhibitor of Pawpaw Leaves Extract - Omotioma,M. (2016)
Modeling the corrosion inhibition of mild steel in HCl medium with inhibitor of pawpaw leaves extract is presented. The extract was analyzed using gas chromatography-mass spectrometry. Thermometric and gravimetric methods were employed in the corrosion inhibition study. The inhibition efficiency was modeled and optimized using response surface methodology (RSM). It was observed that the free energy of adsorption (ΔGads) was negative and less than the threshold value of -40 kJ/mol. The adsorption of the extract was spontaneous, and occurred according to the mechanism of physical adsorption. A quadratic model was generated, with optimum inhibition efficiency of 80.29% obtained. The extract was highly efficient in the corrosion control process. It is effective for surface treatment of mild steel in the acid medium. Therefore, it is recommended that pawpaw leaves extract should be employed as corrosion inhibitor in oil well acidizing and surface treatment of mild steel.